Postoperative Outcomes Following Tension-Free Vaginal Mesh Surgery for Pelvic Organ Prolapse: A Retrospective Study - Oride, Aki; Kanasaki, Haruhiko; Hara, Tomomi; Kyo, Satoru (Urology Journal, 2019)
Purpose: We retrospectively reviewed the postoperative outcomes of patients who underwent tension-free vaginal mesh (TVM) surgery in our institution. Methods: In total, 195 TVM surgeries were performed at the Shimane University School of Medicine from January 2010 to May 2016 in patients with Pelvic Organ Prolapse–Quantification (POP-Q) stage II or higher. Perioperative complications and problems arising following surgery were assessed from medical charts. Results: Among the 195 patients, only 1 patient required blood transfusion due to massive intraoperative blood loss. None of the patients experienced intraoperative complications, such as injury to the bladder or rectum during surgery. Mesh exposure was observed in 10 patients (5.1%). Overall, 6 of these 10 patients were asymptomatic, and surgical treatment was required in only 1 patient. Mesh exposure occurred at significantly higher frequencies in patients aged less than 60 years. Postoperative recurrence of POP, which was defined as recurrence over POP-Q stage 2, was noted in 13 of the 195 patients (6.6%). Re-operation was performed in 1 patient in whom recurrence was observed within 3 months postoperatively. Recurrence of POP was likely to occur in patients with higher POP-Q stages. Overall, 31 of the 195 patients (15.9%) required medication for postoperative stress urinary incontinence (SUI) after surgery. Among these, 2 patients underwent surgical treatment for SUI. Conclusion: Outcomes following the TVM procedure were satisfactory. However, caution should be exercised against mesh exposure in younger patients and recurrence of POP in patients with advanced POP-Q stage.